Hypertensional Disease Diit, Traditional Treatment And Prevention For Hypertension Disease - Parrela, Riska; Nurhuda, Muh Aldi; setyawati, Devi dewi; Wahyu, Indah (Jurnal Pendidikan Kesehatan, 2021)
Hypertension is an increase in systolic blood pressure of at least 140 mmHg or diastolic pressure of at least 90 mmHg. Hypertension will be at risk of stroke, heart attack, heart failure, and is the main cause of chronic heart failure. Traditional treatment of hypertension is recommended for people with hypertension. The purpose of this research is to determine the history of hypertension in the elderly in the surrounding area. This study is a literature review using the pubmed search tool. The key word used is traditional hypertension treatment. From the results of research on hypertension sufferers, we analyzed that most hypertension sufferers had not yet implemented a prohibited diet